Book Review: Language Curriculum Design - Iswahyudi, Sabrina Retnasari (Celebes Journal of Language Studies, 2022)
This is a review of a book entitled Language Curriculum Design by I.S.P Nation & John Macalister. It provides analysis and criticism of the language curriculum design. The language curriculum design book describes the process of curriculum creation in detail and offers chances for practice and application. Since creating a curriculum or course is primarily a "how-to" activity, a significant portion of this book is devoted to describing the processes involved in the curriculum design process as well as elaborating on and justifying these procedures. The book also offers chances for practicing and putting the steps into practice. The key phases in the curriculum design process are covered in Chapters 2 to 8, which give a summary of those chapters. Numerous approaches to covering these tasks are described in Chapter 9. In chapters 10 through 14, The course covers important aspects of curriculum design, such as including students in the process, selecting and changing the course contents, innovation theory, retraining the instructors, and assisting teachers and students in using the course. Despite the fact that curriculum design is a "how-to-do-it" activity, the procedures must be explained in general terms so that they may be used in a variety of unique settings. Tasks that help readers to connect the stages to their own experiences are provided in each chapter, along with a case study and recommendations for more reading. When good theory and cutting-edge practice are combined, language learning may be Globally, ESL/EFL language instruction programs can use curriculum design in many different ways.